1986
DOI: 10.1016/0014-5793(86)80659-7
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone production by mouse Leydig cells is stimulated in vitro by atrial natriuretic factor

Abstract: The synthetic atria1 peptides, rat atria1 natriuretic peptide, atriopeptin I and atriopeptin II, stimulated testosterone production by mouse Leydig cells in a time-and concentration-dependent manner. The maximum stimulation of the steroidogenesis in response to the peptides was 6lo-fold over the basal level, as compared with 20-24-fold stimulation obtained with saturating concentrations of hCG. The stimulation of steroidogenesis by the most potent peptide, atriopeptin II, was markedly enhanced in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…Our results indicated that digitoxin have the inhibitory effect on the testicular function both in vivo and in vitro. This effect may partly result from the increased secretion of atrial natriuretic peptide (ANP) from atrial myocytes, and ANP can exert a potent direct inhibitory effect on testicular function [Mukhopadhyay et al, 1986;Foresta et al, 1993]. In addition, this study showed that digitoxin can act directly on the testicular interstitial cells to inhibit the secretion of testosterone (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Our results indicated that digitoxin have the inhibitory effect on the testicular function both in vivo and in vitro. This effect may partly result from the increased secretion of atrial natriuretic peptide (ANP) from atrial myocytes, and ANP can exert a potent direct inhibitory effect on testicular function [Mukhopadhyay et al, 1986;Foresta et al, 1993]. In addition, this study showed that digitoxin can act directly on the testicular interstitial cells to inhibit the secretion of testosterone (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…An early study suggested that long-term digoxin therapy may also depress LH secretion by the pituitary gland (Tappler & Katz, 1979), a phenomenon which would be expected to exacerbate the direct inhibitory actions of the drug on testicular testosterone secretion. Similarly, the digoxininduced blockade of testosterone synthesis in vivo may be reinforced by the concomitant fall of atrial natriuretic peptide (ANP), a peptide which stimulates testosterone secretion in vitro in a time and concentration-dependent manner (Mukhopadhyay et al, 1986;Foresta & Mioni, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…A potential role for ANF in the maturation of the oocyte was previously suggested by the demonstration of ANF receptors in mammalian gonads [3,4,19] and the ability of these receptors to mediate ANF-induced increases in steroid production. The peptide stimulates testosterone production in mouse interstitial cells [20] and enhances both basal and gonadotropin-stimulated testosterone secretion from mouse Leydig cells [21]. ANF also enhances LH-induced progesterone secretion in cultured ovarian granulosa-lutein cells [22].…”
Section: Potentiation Of Oocyte Maturationmentioning
confidence: 97%